Effect Of Health Education Through Demonstration On Tooth-Brushing - Heni Fa'riatul Aeni; Nuryati; Diding Syarifudin (Media Informasi, 2026)
Plaque and food debris can easily accumulate on the teeth and gums if proper brushing is not practiced regularly. Health education through demonstration is an approach expected to improve tooth-brushing behavior among school children. This study aimed to determine the effect of health education using the demonstration method on tooth-brushing behavior among Grade 1 students at MI Luwunggede, Brebes District. This study employed a quantitative quasi-experimental design using a one-group pre–post test approach. A total of 65 students were selected using total sampling. An observation sheet assessing tooth-brushing behavior was used as the research instrument. Data were analyzed using univariate analysis and the Wilcoxon signed-rank test for bivariate analysis. The pre-test results showed that most respondents were in the poor category (73.8%). After the intervention, most respondents were in the good category (56.9%). The Wilcoxon test indicated a statistically significant difference before and after intervention (p < 0.001). It can be concluded that health education through demonstration significantly improved tooth-brushing behavior among students. Regular school-based oral health education programs are recommended to maintain sustainable behavioral change